Effects of a short-term detraining period on the strength deficit and functional performance of highly trained soccer players - Loturco, I.; Grazioli, R.; Veeck, F.; Nakamura, F. Y.; Inácio, M.; Schons, P.; Preissler, A.; Pinto, R. S.; Pereira, L. A.; McGuigan, M. R.; Cadore, E. L. (The Journal of Strength and Conditioning Research, 2023)
The aim of this study was to examine the effects of a 4-week detraining period on the neuromuscular performance of highly trained soccer players. Pre and post detraining, 18 adult soccer players (age: 27 ± 4.9 years; height: 180.2 ± 7.1 cm; body mass [BM]: 78.9 ± 7.6 kg) performed vertical jumps, 20-m linear sprints, curve sprint and change of direction speed tests, and a progressive loading test in the half-squat exercise with loads corresponding to 50, 100, and 150% of the players' BM to assess the peak-force (PF), mean power (MP), and strength-deficit (SDef). Pre and post differences in the variables of interest were analyzed using paired t-tests and effect sizes (ES). No significant changes were detected for vertical jumping height and sprint times. Higher PF at 50 and 100% BM and lower SDef were shown when comparing pre- and postassessments (ES = 0.66, 0.68, 0.55; p = 0.018, 0.016, and 0.046, respectively). The MP at 50 and 100% BM increased significantly after the detraining phase (ES = 0.56, 0.82; p = 0.049 and 0.007, respectively). The results indicate that these athletes were able to maintain and achieve satisfactory levels of performance after a short period of training cessation. Interestingly, some strength- and power-derived parameters improved significantly after short-term detraining, which may have important implications for training programs aimed at maximizing speed and power performance. It is recommended that coaches test their players not only at the beginning but also at the end of the season, to better evaluate variations in performance and thus create more efficient and tailored training strategies.